The Jemima code : two centuries of African American cookbooks - Tipton-Martin, Toni (University of Texas Press, 2015)
Women of African descent have contributed to America's food culture for centuries, but their rich and varied involvement is still overshadowed by the demeaning stereotype of an illiterate "Aunt Jemima" who cooked mostly by natural instinct. Tipton-Martin looks at black cookbooks that range from a rare 1827 house servant's manual, the first book published by an African American in the trade, to modern classics. These cookbooks offer firsthand evidence that African Americans cooked creative masterpieces from meager provisions, educated young chefs, operated food businesses, and nourished the African American community through the long struggle for human rights.